A taxonomy of innovation networks - Benjamin Schön; Andreas Pyka (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2012)
In this discussion paper we develop a theory-based typology of innovation networks with a special focus on public-private collaboration. This taxonomy is theoretically based on the concept of life cycles which is transferred to the context of innovation networks as well as on the mode of network formation which can occur either spontaneous or planned. The taxonomy distinguishes six different types of networks and incorporates two plausible alternative developments that eventually lead to a similar network structure of the two types of networks. From this, important conclusions and recommendations for network actors and policy makers are drawn.
urn:nbn:de:bsz:100-opus-6724
Keywords: 330